(untitled) (Development Service Industry Management, 2025)
The article considers the interpretation of the concept of economic security of an enterprise, which has been proposed by both foreign and domestic scientists, and offers its own interpretation. External threats to the economic security of tourism enterprises in Ukraine have been identified and analyzed: political, economic, social, technological, legal, environmental, which were systematized using PESTLE analysis. The advantage of using such a methodological approach is the identification of not only existing threats that hinder the development of tourism enterprises in Ukraine, but also those that may have a significant impact on them in the future. To ensure the economic security of tourism enterprises in Ukraine, it is proposed to take into account the results of the study when developing their own development strategies and the new Strategy for Economic Security of Ukraine